One hundred years of solitude - d; Rabassa, Gregory (New York : Harper Perennial Modern Classics, 2006)
Tells the story of the Buendia family, set against the background of the evolution and eventual decadence of a small South American town.
Originally published by Harper & Row in 1970.
Includes "P.S. insights, interviews & more..."
Keywords: Macondo (Imaginary place) -- Fiction; Latin America -- Social conditions -- Fiction